1-Methyl-4-[(E)-2-(2-thienyl)ethenyl]pyridinium 4-chlorobenzenesulfonate - Chantrapromma, Suchada (International Union of Crystallography, 2008)

(untitled)
In the title compound, C(12)H(12)NS(+)·C(6)H(4)ClO(3)S(−), the cation is almost planar and exists in the E configuration. The cations and anions form alternate layers parallel to the ab plane. Within each layer, both cations and anions form chains directed along the b axis. The molecules are interconnected by weak C—H⋯O interactions into a three-dimensional network. The crystal structure is further stabilized by C—H⋯π interactions involving the thiophene ring. The sulfonate and thiophene groups are involved in weak intramolecular C—H⋯O and C—H⋯S interactions, respectively. The latter intramolecular hydrogen bonds produce S(5) ring motifs.